Canine parvovirus type 2 (CPV-2) and bacterial coinfections in dogs: phenotypic and genotypic resistance profiles in northern Kazakhstan - Aleshina, Yuliya; Zhabykpayeva, Aigul; Abilova, Zulkyya; Yerzhanov, Yertay; Nechaev, Andrey; Madiyev, Daniyar; Bermukhametov, Zhanaidar; Rychshanova, Raushan (Frontiers in Veterinary Science, 2026)
IntroductionCanine parvovirus type 2 (CPV-2) poses a serious viral threat to dogs. Despite the potential contribution of companion animals to antimicrobial resistance, data on CPV and associated bacterial coinfections remain limited. This study aimed to characterize the CPV-2 epizootic situation in Kostanay (Kazakhstan), assess bacterial coinfections and AMR profiles, including molecular markers, and evaluate their relevance to One Health.MethodsEpizootiological monitoring revealed a CPV-2 positivity rate of 19.4% (n = 549). For microbiological and PCR studies, two groups were established: CPV-2+ (n = 198) and clinically healthy (n = 200) dogs. E. coli, Klebsiella spp., and S. aureus were identified by culture/MALDI-TOF; AMR was assessed by disc diffusion (CLSI). Resistance genes were detected by PCR: for Enterobacteriaceae, blaTEM, OXA, tetA/tetB, StrA/StrB, aadB, aphA1, qnr/qepA, and sul1/sul3; for S. aureus, blaZ, ermB/ermC, tetK/tetM, and mecA.ResultsA total of 131 isolates were obtained (CPV-2+: 72; healthy: 59), predominantly E. coli (n = 65) and S. aureus (n = 53). CPV-2+ dogs tended to carry more gram-negative bacteria. Enterobacteriaceae were highly resistant to tetracyclines (58.4%) and fluoroquinolones (51.2%), and sporadic carbapenem resistance was detected in Klebsiella (7%). β-Lactamase determinants (blaTEM/OXA) and aminoglycoside resistance genes were more frequently detected in CPV-2+ isolates, whereas blaZ predominated in S. aureus.ConclusionCPV-2 infection is associated with a significant bacterial burden and pronounced AMR, supporting the need for improved surveillance and empirical therapy optimization. These results fill a geographical data gap in Central Asia and align with AMR trends reported in Europe and Asia, underscoring the cross-border circulation of CPV-2 and resistant bacteria and the need for a One Health approach.